2020
DOI: 10.3390/cells9051263
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Associated Heat Shock Proteins in Oncology: From Basic Research to New Theranostic Targets

Abstract: Heat shock proteins (HSPs) constitute a large family of conserved proteins acting as molecular chaperones that play a key role in intracellular protein homeostasis, regulation of apoptosis, and protection from various stress factors (including hypoxia, thermal stress, oxidative stress). Apart from their intracellular localization, members of different HSP families such as small HSPs, HSP40, HSP60, HSP70 and HSP90 have been found to be localized on the plasma membrane of malignantly transformed cells. In the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 180 publications
(247 reference statements)
1
44
0
Order By: Relevance
“…Whereas, HSP60 (HSPD1) is found in mitochondria [ 74 ]. Some HSPs can also be found on the cell surface, such as HSP60 and HSP70, especially in lipid rafts (plasma membrane subdomains, containing high levels of cholesterol and glycosphingolipids) [ 75 ]. More recently, HSPs are considered key players in the intercellular cross-talk [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, HSP60 (HSPD1) is found in mitochondria [ 74 ]. Some HSPs can also be found on the cell surface, such as HSP60 and HSP70, especially in lipid rafts (plasma membrane subdomains, containing high levels of cholesterol and glycosphingolipids) [ 75 ]. More recently, HSPs are considered key players in the intercellular cross-talk [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HSF and HSP can be an important target for MDR reversibility [ 49 , 50 ]. Numerous studies have shown the relationship between membrane-associated HSP and drug resistance and the possibility to use HSP as biomarkers for tumor detection [ 51 ]. The results of our study showed that the basal level of expression of the hsc70 and grp78 genes was significantly higher in RJKEB cells with MDR phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Hsps perform important functions in maintaining protein homeostasis, such as mediating protein folding, assembly, and intracellular localization and regulating apoptosis. Failure of these processes may lead to disease ( 1 ).…”
Section: Introductionmentioning
confidence: 99%